Evaluation and Development of Web-Based Information Systems of Unit Pelaksana Teknis Mengwi District Based on Usability Method and User Experience - I Made Suryana Dwipa; I Made Candiasa; Luh Joni Erawati Dewi (IJISTECH (International Journal of Information System and Technology), 2021)
Unit Pelaksana Teknis (UPT) of Mengwi District is one of the regional agencies of Badung Regency. UPT Mengwi has an important task in terms of educational services in the Mengwi District. There were several problems found by users, namely problems related to the interface and some functional systems that did not run optimally. Therefore, continuous evaluation and development were needed. The evaluation of SIUPT Mengwi was carried out using the evaluation techniques of Performance Measurement, Retrospective Think Aloud, and User Experience Questionnaires. The results in the initial evaluation phase with the Performance Measurement technique showed that it was still not effective and efficient. The analysis of user satisfaction on the attractiveness aspect was 1.45, clarity aspect was 1.05, efficiency aspect was 1.21, and accuracy aspect was 1.45. It discovers that the satisfaction Level of the SIUPT Mengwi has not reached the set standard, so that development efforts were needed. The results of the evaluation after the development phase showed that SIUPT has been effective and efficient with a failure rate of 0%, and there was no significant difference in the time to complete the task. All aspects of user satisfaction gained a very good category with an average score for the attractiveness aspect, which was 2.39, the clarity aspect was 2.29, the efficiency aspect was 2.50, the accuracy aspect was 2.41, the stimulation aspect was 2.43, and the novelty aspect was 2.40. For future evaluation and development, some improvements can be made to the Graphic User Interface (GUI) on the system to improve the research which will be carried out.